Price vs. Value of Marine Monitoring - Nygård, Henrik; Oinonen, Soile; Hällfors, Heidi A.; Lehtiniemi, Maiju; Rantajärvi, Eija; Uusitalo, Laura (Frontiers in Marine Science, 2016)
Monitoring data facilitate the basic understanding of changes taking place in nature and provide information for making management decisions, but environmental monitoring is often considered expensive. Here, we apply the concept of value of information to evaluate the value of marine monitoring in the EU Marine Strategy Framework Directive context. We estimated the costs of the Finnish marine monitoring program and used the costs and economic benefits estimates of the Finnish marine strategy to assess the value of environmental monitoring. The numbers were applied to scenarios with different levels of information available prior to management decision-making. Monitoring costs were related to the value of perfect information prior to the management decision, assuming that managers will choose the management option that maximizes the benefits. The underlying assumptions of the conceptual model are that more accurate information about the status facilitates the selection of an optimal set of measures to achieve the environmental objectives and the related welfare gains from the improved environmental status. Our results emphasize the fact that monitoring is an essential part of effective marine management. Importantly, our study show that the value of marine monitoring data is an order of magnitude greater than the resources currently spent on monitoring and that an improved knowledge base can facilitate the planning of more cost-effective measures.